(untitled) (Al-Academy, 2024)
Evaluation is an important basis in the learning and teaching process because of its importance in determining the value of the work and the amount of educational goals achieved. Evaluation depends on measurement and is closely linked to it.Evaluation includes issuing judgment in multiple educational fields. The evaluation process requires addressing the elements of weakness to improve the level, raise its level and quality, and strengthen the elements of strength, acknowledge them, and reward them. And here lies the problem of research, as evaluating the teacher’s performance is one of the necessities of the educational process. It aims to achieve several goals, including achieving goals, providing important outputs for the purposes of research and development, and diagnostic, therapeutic, and preventive purposes that give the teacher feedback on his educational performance and the effectiveness of his teaching.Educators define it as an organized process for collecting and analyzing information for the purpose of determining the degree of achieving goals and making decisions regarding them. The importance of the current research lies in establishing scientific foundations and evaluative criteria to be a basis on which It is used to evaluate the performance of the arts branch teacher, to benefit from it in making educational decisions.The aim of the current research is ( to build a model to evaluate the performance of the arts branch teacher in middle school )In designing her research tool, the researcher relied on several areas, the most important of which are the general objectives and the theoretical framework of the research, which included the basics of the evaluation process, the types of evaluation, its approaches and levels, the stages of evaluating behavior and educational performance, and some evaluation models. In addition to the role and functions of the teacher, teaching skills, educational competencies, and the most important aspects that must be taken into account in consideration when evaluating the teacher’s work.A model was built to evaluate the teacher’s performance to facilitate educational decisions and obtain comprehensive useful information for judging alternatives to decisions, in order to achieve the goal of the research.Also the most important conclusions were :1- The teacher is evaluated in all his aspects in this model, as the evaluation is considered comprehensive. 2- Evaluation contributes to analyzing the teacher’s work.